2018
DOI: 10.1002/brb3.962
|View full text |Cite
|
Sign up to set email alerts
|

The influence of THC:CBD oromucosal spray on driving ability in patients with multiple sclerosis‐related spasticity

Abstract: BackgroundDriving ability is a key function for the majority of patients with multiple sclerosis (MS) to help maintain daily interactions. Both physical and cognitive disability, as well as treatments, may affect the ability to drive. Spasticity is a common symptom associated with MS, and it may affect driving performance either directly or via the medications used to treat it. In this article, we review the evidence relating the antispasticity medicine, Δ9‐tetrahydrocannabinol:cannabidiol (THC:CBD) oromucosal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 48 publications
(94 reference statements)
0
16
0
Order By: Relevance
“…After the optimization of preparation and delivery methods, another product, called Cannador ® , came to the market, delivering Δ9-THC:CBD within a narrow concentration range and at a two-to-one ratio, in the form of an orally administered capsule [ 45 ]. In relation to this, many of the recent studies on medical cannabis have focused on various forms of Δ9-THC + CBD administration [ 46 , 47 , 48 , 49 ] and co-administration of Δ9-THC with first-line neurotherapeutic drugs [ 50 ]. On the other hand, the synthesis of Δ9-THC analogs is another effective way to avoid or reduce its severe side effects.…”
Section: Phytocannabinoids and Synthetic Cannabinoidsmentioning
confidence: 99%
“…After the optimization of preparation and delivery methods, another product, called Cannador ® , came to the market, delivering Δ9-THC:CBD within a narrow concentration range and at a two-to-one ratio, in the form of an orally administered capsule [ 45 ]. In relation to this, many of the recent studies on medical cannabis have focused on various forms of Δ9-THC + CBD administration [ 46 , 47 , 48 , 49 ] and co-administration of Δ9-THC with first-line neurotherapeutic drugs [ 50 ]. On the other hand, the synthesis of Δ9-THC analogs is another effective way to avoid or reduce its severe side effects.…”
Section: Phytocannabinoids and Synthetic Cannabinoidsmentioning
confidence: 99%
“…115 CB1 receptors may also be involved given their abundance in the central nervous system. 116 MC and cannabinoid-based medicines are currently being investigated and used to treat MS-associated spasticity, [117][118][119] but whether they can modify the neuroinflammation that causes progressive disability is still an open question: however, even if they cannot induce robust immunosuppression, they could still help by inhibiting the glial responses that facilitate neurodegeneration. 120…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 99%
“…79 A meta-analysis of studies using the orally administered CBD: THC mixture in nabiximols identified that there appeared to be an improvement in driving ability, probably due to reduced spasticity. 80 Guidance for police services and employers concerning the consumption of Cannabis and the effects of THC, in particular, tends to err towards a pragmatic approach of zero tolerance, although the practicalities of testing for relevant metabolites in biological samples are still being resolved.…”
Section: Barrier 4: Consistency Of Delivery and Pharmacokineticsmentioning
confidence: 99%